PENGARUH FIRM SIZE, LEVERAGE, DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Putri, Tiffani Dwi; Makhdalena, Makhdalena; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to reexamine and analyze the influence of company size, leverage and net profit margin on the profit growth of mining companies in the coal sub sector on the Indonesia Stock Exchange. The population of this research is the coal sub-sector mining companies on the Indonesia Stock Exchange (BE), totaling 8 companies. This research uses purposive sampling with the observation year 2019-2022 and has complete data in accordance with the research objectives which cover 32 years of observation. The form of data from this research is secondary, obtained using documentation techniques sourced from ICMD. The data analysis method in this research uses path analysis with the help of the SPSS program package. The results of this research show that company size have a positive influence on profit growth, leverage not have a negative influence on profit growth while net profit margin has a positive influence on profit growth. The results of this research are expected to be useful for: (1) Companies must be able to increase profits every year by using assets optimally, reducing company costs and reducing debt (2) Investors, by using the voice they have, must pay more attention to the components that influence profit (3) Academics, can provide input in learning financial accounting material, especially discussions regarding financial report analysis material.Keywords: Firm size, leverage, net profit margin, profit growth